The postharvest ripening of strawberry fruits induced by abscisic acid and sucrose differs from their in vivo ripening. (1st July 2020) - Siebeneichler, Tatiane Jéssica; Crizel, Rosane Lopes; Camozatto, Gustavo Henrique; Paim, Bruna Trindade; da Silva Messias, Rafael; Rombaldi, César Valmor; Galli, Vanessa
Highlights: Postharvest ripening of strawberry is dependent on abscisic acid. Sucrose and abscisic acid treatments accelerated the accumulation of anthocyanins. Sucrose application induces the content of fructose and glucose in the fruits. Exogenous application of abscisic acid induces its synthesis and glycosylation. Mannitol delays postharvest ripening similar to an abscisic acid inhibitor. Abstract: In this study, we compared the chemical composition of strawberry ( Fragaria × ananassa ) fruits that were ripened in vivo (attached to plant) to those ripened during postharvest storage. The effects of the application of abscisic acid (ABA) and sucrose on the postharvest ripening were also evaluated. The results suggested that the postharvest ripening process was dependent on the signal triggered by ABA and differed from in vivo ripening, resulting in fruits with altered chemical composition and firmness. The application of sucrose in unripe strawberries resulted in the induction of ripening, which is dependent on ABA and its derivatives. This induction was more pronounced during the first days of storage and associated with the application of mannitol rather than water, suggesting that mannitol negatively regulated the postharvest strawberry ripening. These results provide further insights into the role of ABA and sucrose in the regulation of postharvest ripening of strawberry.